An intellectual among the chilean theoretical-political swings: Ricardo Latcham Cartwright - Pacheco Garrido, Víctor (2020)
At the end of the 19th century and beginning of the 20th, positivism spread throughout Latin America, achieving a strong consolidation in Chile, where the political and social fluctuations had prepared the liberals to implant their ideas, consolidate their vision about the national state and complete the annexation of the indigenous territory. In this process, the arrival of several European intellectuals to the national territory was the starting point of the academic organization of the social sciences, being Ricardo Latcham undoubtedly one of the most important. His anthropological and archaeological work was the starting point of scientific social science in the country, generating an extensive bibliography of importance to this day. The following article seeks to describe the political and scientific context of the time and how Ricardo Latcham became one of the most important names in Chilean anthropology. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001